Russia-EU28 and Russia-China trade interdependence vs. the competitiveness of the Russian economy - Krzysztof Falkowski (Institute of Economic Research (IER), 2017)
Research background: The actual position of a country in the international division of labour is determined by the competitiveness of its trade, the structure of which may both reveal and perpetuate the comparative advantages possessed. This is particularly true for Dutch disease economies such as Russia. Recently, economic literature has seen a growing interest in the topic of Russia's economic relations with the European Union and China. This article is meant to be the author's contribution to this discussion. Purposes of the article: (1) to discuss the existing trade interdependence between Russia and EU28, and Russia and China; (2) to try to assess the extent to which the current structure of Russian trade with these two partners corresponds with the competitiveness of the Russian economy. Methodology/methods: An in-depth analysis of Russia-EU28 and Russia-China trade interdependencies in 2007-2015 has been conducted, with emphasis on the categories of goods within the spectrum from low-tech to high-tech, according to the OECD classification. Furthermore, in order to analyse Russia's competitive profile with regard to the same categories of goods, Balassa's methodology of revealed comparative advantages has been applied. Findings & Value added: In the recent years, a growing importance of China in Russian trade can be observed, being the effect of dynamic growth of Chinese economy, cooling political relations between Moscow and Brussels and the drop in petroleum prices in international markets. Sadly, the existing structure of Russian trade with EU28 and China seems likely to preserve its traditional competitive advantages in the medium-low-tech goods and petroleum, which, in turn, will only further exacerbate the negative effects of the so-called Dutch disease affecting the Russian economy.
Keywords: F14; F40; P45; 330; trade interdependence; competitiveness; competitive advantages; Russia; European Union; China